An Alternative Treatment of Secondary Products in Input-Output Analysis: Frustration - ten Raa, Thijs (The Review of Economics and Statistics, 1988)
ten Raa, Chakraborty and Small (1984) rule out industry technology based input-output coefficients in favor of a construct based on the commodity technology model. The latter, however, produces negative coefficients. This note shows that the negatives cannot be ascribed to errors of measurement. The very framework of deriving unique technical coefficients matrices from the black-box of a single pair of input and output flows must be abandoned.